Education and the COVID-19 Pandemic: A Critical Discourse Analysis of Indonesian Merdeka Curriculum English Textbooks: Penelitian - Andi Sahtiani Jahrir; Edi Sam (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study analyzes the ideological construction of COVID-19 discourse within Grade XI English textbooks under Indonesia's Merdeka Curriculum. Employing Critical Discourse Analysis (CDA) based on Norman Fairclough's model, this research investigates how the textbooks represent social actors (government, health workers, citizens), actions, and values related to the pandemic. Analysis of a text titled "Benefits of COVID-19 Vaccination" reveals persuasive linguistic strategies, such as the use of modality, rhetorical questions, and metaphors, subtly encouraging compliance and social responsibility towards vaccination. Findings indicate that the text is not merely informative but also ideologically charged, reinforcing public health narratives, social responsibility, and the legitimacy of state authority. This study highlights the role of textbooks as tools of ideological reproduction, demonstrating how language can be used to align students' awareness with state-supported views, neglecting critical thinking in favor of moral obligation and compliance. This research contributes to a broader understanding of how language and ideology intersect to shape educational experiences and social values in the post-pandemic era.